2013
DOI: 10.5812/ircmj.6409
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Sperm Parameters With Semen Lipid Peroxidation and Total Antioxidants Levels in Astheno- and Oligoasheno- Teratospermic Men

Abstract: Background: Sperm dysfunction caused by reactive oxygen species (ROSs) is one of the major causes of infertility in men, which leads to, lipid peroxidation (LPO) and the formation of stable peroxidation products like Malondialdehyde (MDA) in seminal plasma. MDA is effective factor in reducing fertility. Objectives: The aim of this study is to determine two biochemical markers of oxidative stress; TAC and MDA, and them correlation to quality-quantity factors in Asthenoteratospermic and Oligoashenoteratospermic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 44 publications
2
50
0
3
Order By: Relevance
“…In addition, they documented higher MDA levels in the seminal plasma of asthenoteratozoospermic and oligoasthenoteratozoospermic men and MDA's negative correlation with sperm count, motility, and normal morphology (21). In another study, Patel et al observed elevated levels of MDA in all infertile groups, except the azoospermic group, compared to fertile men.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, they documented higher MDA levels in the seminal plasma of asthenoteratozoospermic and oligoasthenoteratozoospermic men and MDA's negative correlation with sperm count, motility, and normal morphology (21). In another study, Patel et al observed elevated levels of MDA in all infertile groups, except the azoospermic group, compared to fertile men.…”
Section: Discussionmentioning
confidence: 82%
“…Because spermatozoa possess high amounts of polyunsaturated fatty acids in their plasma membranes, they are predisposed to oxidative injury. Therefore, they are susceptible to radical attack and consequently to lipid peroxidation in the plasma membrane (8,21). ROS could also induce base alterations, DNA strand breaks, DNA cross-links, and chromosomal rearrangements (22).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive amounts of ROS may lead to lipid peroxidation, loss of motility, and sperm DNA damage (20,21). There are high amounts of polyunsaturated fatty acids in the plasma membranes of spermatozoa, therefore, they are predisposed to oxidative damage (5,22). In addition, ROS could induce base alterations, DNA strand breaks, DNA cross-links, and chromosomal rearrangements (23).…”
Section: Discussionmentioning
confidence: 99%
“…OS has been found to promote a dose-dependent increase of tyrosine nitration and S-glutathionylation in the sperm, and this change relates to an alteration in motility and the ability of spermatozoa to undergo capacitation [24]. Lipid peroxidation (an indicator of oxidative status) and decreased antioxidant capacity in the ejaculate lead to low motility in asthenoteratozoospermic and oligoasthenoteratozoospermic men; morphology and sperm count were also lower [25]. We found no significant differences in sperm motility between asthenozoospermic and normozoospermic patients among the cases with high and very high OS (52 vs 41.7 %; Table 1), in agreement with a recent study, where no significant correlation was reported between ROS production and sperm motility [26].…”
Section: Relationship Between Ros and Seminal Parametersmentioning
confidence: 99%